Penyertaan Modal Perseroan Terbatas Sebagai Alternatif Strategi Penggalangan Dana Organisasi Kemanusiaan Dengan Legalitas Yayasan - Adi Kurniawan; Ety Rahayu (LPPM Universitas Ekasakti Padang, 2024)
In carrying out its activities, human service organizations need funding for the implementation of planned programs and develop and enlarge the scale of the organization. Currently, there are many fundraising strategies that can be carried out by human service organizations, one of the strategies that can be carried out by humanitarian organizations is to form a prospective business, while the business is carried out through capital participation in a limited liability company. Legally, capital participation in this limited liability company is legalized for human service organizations with the legality of the foundation, even it is regulated directly in the provisions of the law on foundations. The profits obtained can be a source of permanent funding for the organization, so that human service organizations can be independent and survive and meet all organizational needs. However, fundraising strategies by forming businesses like this are not very popular, generally human service organizations still use conventional fundraising patterns, which fully rely on the generosity of donors to meet the needs of the organization.